Atividade antifúngica, mecanismo de ação, citotoxidade e ação antibiofilme da cloramina T sobre Candida spp. - Ferreira, Gabriela Lacet Silva (2015)
Introduction: Faced with limitations to the use of sodium hypochlorite in the disinfection of dental prostheses and the need to control fungal proliferation in these sites, it is necessary to study new substances for this purpose. Objectives: To evaluate the antifungal activity, mechanism of action, cytotoxicity and antibiofilm action of chloramine T (CAT) on Candida spp. The minimum inhibitory concentration (MIC) of the substance on Candida albicans, Candida tropicalis, Candida krusei and Candida glabrata was determined by the microdilution technique and the minimum fungicidal concentration (CFM) was calculated through the subculture in Sabouraud Dextrose Agar (ASD) . The growth inhibition kinetics of C. albicans were evaluated by the method of counting colony forming units (CFU) at different times and concentrations. A microculture of C. albicans was performed on fowl agar plus tween 80 to evaluate the possible alteration of micromorphology against different concentrations of the substance. The possible mechanism of action on wall and fungal cell membrane was verified by the determination of MIC in the presence of sorbitol and ergosterol respectively. The inhibition of the initial adherence of fungal cells, formation and reduction of C. albicans biofilm were evaluated after short (1 min) and prolonged (8 h) contact with the substance and formation of the biofilm was measured by absorbance at 600 nm, Transformed into scores referring to the percentage of inhibition obtained based on the values ​​of the control group. The cytotoxicity of the substance was evaluated by the hemolysis method. Nystatin and sodium hypochlorite were used as positive controls. A descriptive and inferential analysis was performed considering α = 5%. Results: The CIM75% found for CAT was 781.3 μg / mL and the CFM / MIC ratio suggests a fungicidal activity against most of the strains tested, with probable action on cell wall and membrane. The substance showed immediate and prolonged action on the kinetic test and caused reduction of the filamentous form and inhibition of chlamydoconidia. In the biofilm assay, it presented similar results to sodium hypochlorite for inhibition of initial adherence and formation of mature biofilm (p> 0.05) and was more effective in reducing mature biofilm in the short contact groups at MIC concentration x2 (24 H) and CIM x 4 (48 h) (p <0.05). Conclusion: CAT shows antifungal activity on Candida spp. And shows fungicidal action on most of the strains tested. Its action is immediate and prolonged in the inhibition of C. albicans growth and probably occurs both in the wall and in the cell membrane. CAT causes alterations in the micromorphology of C. albicans and has antibiofilm activity, being effective in inhibiting the initial adherence of fungal cells, as well as in the formation and reduction of biofilm.